A community-based primary prevention programme for type 2 diabetes mellitus integrating identification and lifestyle intervention for prevention: a cluster randomised controlled trial - Melanie J Davies; Laura J Gray; Dariush Ahrabian; Marian Carey; Azhar Farooqi; Alastair Gray; Stephanie Goldby; Sian Hill; Kenneth Jones; Jose Leal; Kathryn Realf; Timothy Skinner; et al. (NIHR Journals Library, 2017)
Background: Prevention of type 2 diabetes mellitus (T2DM) is a global priority; however, there is a lack of evidence investigating how to effectively translate prevention research into a primary care setting. Objectives: (1) To develop and validate a risk score to identify individuals at high risk of T2DM in the UK; and (2) to establish whether or not a structured education programme targeting lifestyle and behaviour change was clinically effective and cost-effective at preventing progression to T2DM in people with prediabetes mellitus (PDM), identified through a risk score screening programme in primary care. Design: A targeted screening study followed by a cluster randomised controlled trial (RCT), with randomisation at practice level. Participants were followed up for 3 years. Setting: A total of 44 general practices across Leicestershire, UK. The intervention took place in the community. Participants: A total of 17,972 individuals from 44 practices identified through the risk score as being at high risk of T2DM were invited for screening; of these, 3449 (19.2%) individuals attended. All received an oral glucose tolerance test. PDM was detected in 880 (25.5%) of those screened. Those with PDM were included in the trial; of these, 36% were female, the average age was 64 years and 16% were from an ethnic minority group. Intervention: Practices were randomised to receive either standard care or the intervention. The intervention consisted of a 6-hour group structured education programme, with an annual refresher and regular telephone contact. Main outcome measures: The primary outcome was progression to T2DM. The main secondary outcomes were changes in glycated haemoglobin concentrations, blood glucose levels, cardiovascular risk, the presence of metabolic syndrome, step count and the cost-effectiveness of the intervention. Results: A total of 22.6% of the intervention group did not attend the education and 29.1% attended all sessions. A total of 131 participants developed T2DM (standard care, n = 67; intervention, n = 64). There was a 26% reduced risk of T2DM in the intervention arm compared with standard care, but this did not reach statistical significance (hazard ratio 0.74, 95% confidence interval 0.48 to 1.14; p = 0.18). There were statistically significant improvements in glycated haemoglobin concentrations, low-density lipoprotein cholesterol levels, psychosocial well-being, sedentary time and step count in the intervention group. The intervention was found to result in a net gain of 0.046 quality-adjusted life-years over 3 years at a cost of £168 per patient, with an incremental cost-effectiveness ratio of £3643 and a probability of 0.86 of being cost-effective at a willingness-to-pay threshold of £20,000. Conclusions: We developed and validated a risk score for detecting those at high risk of undiagnosed PDM/T2DM. We screened > 3400 people using a two-stage screening programme. The RCT showed that a relatively low-resource pragmatic programme may lead to a reduction in T2DM and improved biomedical and psychosocial outcomes, and is cost-effective. Limitations: Only 19% of those invited to screening attended, which may limit generalisability. The variation in cluster size in the RCT may have limited the power of the study. Future work: Future work should focus on increasing attendance to both screening and prevention programmes and offering the programme in different modalities, such as web-based modalities. A longer-term follow-up of the RCT participants would be valuable. Trial registration: Current Controlled Trials ISRCTN80605705. Funding: The National Institute for Health Research Programme Grants for Applied Research programme.